Magnetic resonance imaging and spectroscopy for differential assessment of liver abnormalities induced by Opisthorchis felineus in an animal model. - Alexandra G Pershina; Vladimir V Ivanov; Lina V Efimova; Oleg B Shevelev; Sergey V Vtorushin; Tatjana V Perevozchikova; Alexey E Sazonov; Ludmila M Ogorodova (Public Library of Science (PLoS), 2017)
European liver fluke Opisthorchis felineus, causing opisthorchiasis disease, is widespread in Russia, Ukraine, Kazakhstan and sporadically detected in the EU countries. O. felineus infection leads to hepatobiliary pathological changes, cholangitis, fibrosis and, in severe cases, malignant transformation of bile ducts. Due to absence of specific symptoms, the infection is frequently neglected for a long period. The association of opisthorchiasis with almost incurable bile duct cancer and rising international migration of people that increases the risk of the parasitic etiology of liver fibrosis in non-endemic regions determine high demand for development of approaches to opisthorchiasis detection.In vivo magnetic resonance imaging and spectroscopy (MRI and MRS) were applied for differential assessment of hepatic abnormalities induced by O. felineus in an experimental animal model. Correlations of the MR-findings with the histological data as well as the data of the biochemical analysis of liver tissue were found. MRI provides valuable information about the severity of liver impairments induced by opisthorchiasis. An MR image of O. felineus infected liver has a characteristic pattern that differs from that of closely related liver fluke infections. 1H and 31P MRS in combination with biochemical analysis data showed that O. felineus infection disturbed hepatic metabolism of the host, which was accompanied by cholesterol accumulation in the liver.A non-invasive approach based on the magnetic resonance technique is very advantageous and may be successfully used not only for diagnosing and evaluating liver damage induced by O. felineus, but also for investigating metabolic changes arising in the infected organ. Since damages induced by the liver fluke take place in different liver lobes, MRI has the potential to overcome liver biopsy sampling variability that limits predictive validity of biopsy analysis for staging liver fluke-induced fibrosis.